Die deutsche Fischerei vor Nordnorwegen und bei der Bäreninsel im Dezember 1996 und im ersten Halbjahr 1997 - Schöne, Rüdiger (1997)
Biological investigations were carried out onboard the German factory trawlers “Wiesbaden” and “Kiel” off the Norwegian coast and at Bear Island from December 1996 to June 1997. Data will be contributed to the assessments ofthe ICES “Arctic Fisheries Working Group”. Information on distribution and fishery of cod, haddock, saithe, redfish and Greenland halibut are given. Biological aspects of length- and age distributions, and stomach- and gonadinvestigations are represented. Some aspects of the function of sorting grids used in the Bear Island fishery are discussed. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010.